Don't Miss This! Red Flags in the Pediatric Eye Examination: Acquired Nystagmus. Issue 3 (3rd July 2019) - Kincade, Madison
ABSTRACT: When a new patient presents with a chief complaint of nystagmus, the clinician must know what further action is necessary in order to identify vision or life-threatening diseases. Some types of acquired nystagmus include upbeat nystagmus, downbeat nystagmus, see-saw nystagmus, and period alternating nystagmus. By identifying the characteristics and causes, acquired nystagmus can be recognized as a "red flag." In contrast, children diagnosed with infantile or physiological nystagmus generally will not need neurological testing. As crucial as it is to recognize acquired nystagmus, it is equally important to differentiate among the specific subtypes and to be familiar with the key features of infantile nystagmus.